Prevalence of sacroiliac dysfunction among patients with Low back pain referring to hospitals in Isfahan (a pilot study) - ZS Rezaeian; F Alifard; Z Goodarzi; A Karimi; M Asgharoi (Vesnu Publications, 2008)
Introduction: Low back pain (LBP) is one of the most common causes of disability that leads to discomfort and imposes heavy expenses on individuals and the society. Sacroiliac joint (SIJ) dysfunction is one of the courses of low back pain and difficult to diagnose. Therefore, it is usually neglected in evaluation and treatment of patients with low back pain. Materials and Methods: This epidemiological study carried out to determine the prevalence of SIJ dysfunction among LBP clients referred to the based hospitals in Isfahan (June to August 2007). According to the previous studies, 114 patients with LBP were selected by simple randomized sampling. Results: The results showed that more than 30 percent of LBP patients suffer from SIJ dysfunction simultaneously. Conclusion: According to this study, it is very important to pay attention to the signs and symptoms of SIJ dysfunction in LBP patients; because any pain relieving factors will satisfy patients from their physiotherapy treatment. Keywords: Sacroiliac joint, Low back pain, Prevalence